2021
DOI: 10.1038/s41423-020-00590-8
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 7 deficiency suppresses type 1 diabetes development by modulating B-cell differentiation and function

Abstract: Innate immunity mediated by Toll-like receptors (TLRs), which can recognize pathogen molecular patterns, plays a critical role in type 1 diabetes development. TLR7 is a pattern recognition receptor that senses single-stranded RNAs from viruses and host tissue cells; however, its role in type 1 diabetes development remains unclear. In our study, we discovered that Tlr7-deficient (Tlr7−/−) nonobese diabetic (NOD) mice, a model of human type 1 diabetes, exhibited a significantly delayed onset and reduced incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 48 publications
(21 reference statements)
0
27
0
Order By: Relevance
“…B cell receptor (BCR) signaling ( 32 , 49 ), is diminished in B cells from individuals with established type 1 diabetes ( 25 , 43 ). Signaling through TLR9 changes the frequency and function of IL-10 producing B cells in NOD mice; TLR9 deficiency specifically in B cells increased IL-10 producing cells and protected against diabetes ( 50 ). No direct study has demonstrated a mechanism that drives a Breg defect in type 1 diabetes in humans however, and this remains an outstanding question (see Discussion and Outstanding Questions ).…”
Section: Breg Induction and Type 1 Diabetesmentioning
confidence: 99%
“…B cell receptor (BCR) signaling ( 32 , 49 ), is diminished in B cells from individuals with established type 1 diabetes ( 25 , 43 ). Signaling through TLR9 changes the frequency and function of IL-10 producing B cells in NOD mice; TLR9 deficiency specifically in B cells increased IL-10 producing cells and protected against diabetes ( 50 ). No direct study has demonstrated a mechanism that drives a Breg defect in type 1 diabetes in humans however, and this remains an outstanding question (see Discussion and Outstanding Questions ).…”
Section: Breg Induction and Type 1 Diabetesmentioning
confidence: 99%
“…Furthermore, in combination with IFNα, TLR7 activation augments IL-6 production and isotype switching in B cells [60]. In NOD mice, TLR7 deficiency delays and reduces the development of autoimmune diabetes and alters the functional responses of B cells [62]. Therefore, it is likely that the heightened expression of IFNα enhances TLR7 expression in B cells situated in the pancreas, and that this, in turn, synergistically amplifies IL-6 and pro-inflammatory cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…The role of TLRs in immune regulation and T1D development has been uncovered by several studies. Deletion of Tlr7 protected NOD mice from T1D, which might be due to the altered differentiation and reduced antigen-presenting functions of B cells ( 21 ). Tlr9 deficient NOD mice exhibited a decreased incidence of T1D.…”
Section: Discussionmentioning
confidence: 99%